Membangun budaya literasi digital dengan menerapkan strategi membaca dan menulis sejak dini di MI Al-huda Tumpang, Blitar - permadani, indriati alia (Maliki Interdisciplinary Journal, 2025)
This study aims to build a digital literacy culture by implementing early reading and writing strategies at MI Al-Huda Tumbang, Blitar. The research method used is descriptive qualitative. The results showed that MI Al-Huda has implemented strategies to build a digital literacy culture at school. The strategy is in the form of implementing a digital literacy program with digital reading and writing habits for students, providing facilities and infrastructure that support digital literacy. The implementation of the strategy shows a positive impact, which is characterized by MI Al-Huda students being accustomed to using digital technology to read, write and search for information. Therefore, this digital literacy program can train students’ abilities for critical thinking, problem solving and collaboration. Furthermore, this study also found that teacher support and the school environment play a crucial role in maintaining consistent implementation of the digital literacy program. Teachers act as facilitators, guiding students in using technology productively and responsibly, while a conducive school environment encourages the creation of a digital-based learning culture. Challenges faced in implementing this program include limited access to technological devices, variations in students’ digital abilities, and the need to improve teachers’ competencies in managing digital learning media. However, through collaboration between the school, teachers, and parents, these obstacles can be minimized. Overall, the implementation of digital literacy strategies at MI Al-Huda Tumpang Blitar has proven effective in fostering interest in digital reading and writing and improving students’ readiness to face the challenges of learning in the 5.0 technology era.